A method for considering road curvature’s impact on aggressive turning - Kai Liu; Haixia Feng; Zhixin Xu; Meng Guo; Xinsen Fan; Qiuxia Li; Zhongke Feng (PLoS ONE, 2025)
Addressing the current issue of not considering the influence of road geometry in the recognition of aggressive turning, a dangerous driving behavior, this paper proposes a method to eliminate the impact of road curvature on the recognition of aggressive turning based on On-Board Diagnostics (OBD) trajectory data and high-precision electronic map data. The method is validated using Jinan City as the study area. The results show that the proposed method effectively removes the influence of road curvature on the recognition of aggressive turning (left or right turns), reduces misjudgments of dangerous driving behaviors of drivers, and enhances the accuracy of identifying drivers’ aggressive turning hazardous behaviors.